2007
DOI: 10.1007/s11033-007-9086-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a male sterility gene homolog BcMS2 from Chinese cabbagge-pak-choi that expressing in an anther-specific manner

Abstract: A male sterility gene homolog, designated BcMS2, was isolated from flower buds using gene-specific primer pairs and was submitted to GenBank under accession number EF093533. Comparison of BcMS2 gene with MS2 from Arabidopsis thaliana and MS2Bnap from Brassica napus revealed some differences in gene structure and evolution. The full genomic DNA sequence of BcMS2 was 2,576 bp in length containing 8 exons and 7 introns, more than those of MS2Bnap but less than MS2. RT-PCR showed that BcMS2 gene expressed only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…napus using RT-PCR technique, and found that there existed an amino acid divergence between fertile S45B and sterile S45A, which may be the putative male sterility site in S45A. Male sterility gene homolog, designated BcMS2 , expressed only in stage III flower buds of male fertile Chinese cabbage-pak-choi “ZUBajh97-01B” and there were no detection in all organs of Polima cytoplasmic male sterility (CMS) line ‘Bpol97-05A’ and Ogura CMS line ‘Bogu97-06A’ [77]. In this study, MS2 members (Bra034793, Bra038691) were only expressed in Fer, whose TPM was 1766.48 and 480.76, respectively, and then it was suggested that the two genes were involved in the development of Fer pollens.…”
Section: Discussionmentioning
confidence: 99%
“…napus using RT-PCR technique, and found that there existed an amino acid divergence between fertile S45B and sterile S45A, which may be the putative male sterility site in S45A. Male sterility gene homolog, designated BcMS2 , expressed only in stage III flower buds of male fertile Chinese cabbage-pak-choi “ZUBajh97-01B” and there were no detection in all organs of Polima cytoplasmic male sterility (CMS) line ‘Bpol97-05A’ and Ogura CMS line ‘Bogu97-06A’ [77]. In this study, MS2 members (Bra034793, Bra038691) were only expressed in Fer, whose TPM was 1766.48 and 480.76, respectively, and then it was suggested that the two genes were involved in the development of Fer pollens.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of NTP303 family members (ntp101, 201, 302 and ntp805) in tobacco affected in vivo pollen tube growth and resulted in male sterile plants (de Groot et al 2004). Several ESTs, such as FB4, FB15, FB20, showed homology to male sterility-related protein from L. usitatissimum, Arabidopsis and Chinese cabbage (Aarts et al 1997;Jiang and Cao 2008;Chen et al 2011a, b). Male Sterile 2 encodes a plastid-localized fatty acyl carrier protein reductase required for pollen exine development in Arabidopsis (Chen et al 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…FB3 and FB46 showed homology to a pollen development related gene, ntp805 (AY366400), in N. tabacum (Hafidh et al 2012). Several ESTs, such as FB4, FB15 and FB20 showed homology to male sterility-related protein from Linum usitatissimum, Arabidopsis and Chinese cabbage (Aarts et al 1997;Jiang and Cao 2008;Chen et al 2011b). F9 showed a similitude with pollen coat-like protein (ABM66381) from Camellia sinensis.…”
Section: Identification Of Genes Involved In Pollen Developmentmentioning
confidence: 99%
“…The study of anther development is important for Chinese cabbage breeding. Though several genes related to anther development have been identified in Chinese cabbage, such as BAN103 3 , BcMS2 4 , BcMF2 5 , BcMF5 6 , BcMF6 7 , BrSKS13 8 , BcMF12 9 , BcMF13 10 , BcMF19 11 , and BcMF20 12 , the molecular mechanism of anther development remains unstudied.…”
Section: Introductionmentioning
confidence: 99%